A TEACHER’S BELIEFS ON THE INTEGRATION OF VIDEO TECHNOLOGY IN TEACHING SPEAKING: A CASE STUDY - Adin Fauzi; Desy Damayanti; Takdir Ilahi (International Journal of Pedagogy and Teacher Education, 2017)
This study investigates the teacher’s beliefs on video technology integration in ELT. A case study was employed as the research design to produce an in-depth description of video technology integration that is rich and holistic. An English teacher was purposefully selected as the research subject of the study. The results of the study indicate that the teacher’s beliefs about English, teaching and learning, and video technology are strongly connected with teaching practices. Moreover, the findings show that there is no any discrepancy between beliefs and practices. This study attempts to contribute to the literature on the study of the teachers’ beliefs that underlie teaching practices. Teachers should understand their own beliefs to promote effective teaching practices.Except where otherwise noted, content on this site is licensed under a Creative Commons Attribution 4.0 International License